2019
DOI: 10.1038/s41598-019-41328-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Hybrid Perovskites Promoted by Chlorine and its Impact on the Performance of Solar Cell

Abstract: The role of Cl in halide hybrid perovskites CH3NH3PbI3(Cl) (MAPbI3(Cl)) on the augmentation of grain size is still unclear although many reports have referred to these phenomena. Herein, we synthesized MAPbI3(Cl) perovskite films by using excess MACl-containing precursors, which exhibited approximately an order of magnitude larger grain size with higher <110>-preferred orientation compared with that from stoichiometric precursors. Comprehensive mechanisms for the large grain evolution by Cl incorporation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 51 publications
0
48
0
1
Order By: Relevance
“…1(a)], the MACl treatment followed by the postannealing at 45°C causes the formation of PbI 2 and Cl-mediated phases. [24][25][26][27] As the postannealing temperature (T Post-Anneal ) is increased to 90°C, these phases disappear in both perovskite compositions, resulting in the impurity-free films as similar to the pristine. Further raise to 110°C results in the additional formation of PbI 2 for MA perovskite, while it is absent for CsFAMA perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)], the MACl treatment followed by the postannealing at 45°C causes the formation of PbI 2 and Cl-mediated phases. [24][25][26][27] As the postannealing temperature (T Post-Anneal ) is increased to 90°C, these phases disappear in both perovskite compositions, resulting in the impurity-free films as similar to the pristine. Further raise to 110°C results in the additional formation of PbI 2 for MA perovskite, while it is absent for CsFAMA perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…While this has led to an improvement in device performance reaching a maximum of 18.2%, the origin of this improvement was predominantly related to an increase in the short-circuit current, with essentially no changes in the V OC . On the other hand, the addition of MACl as an additive, which also leads to larger grain sizes, has been shown to increase the open-circuit voltage of devices leading to a maximum PCE of 17.7% . The use of AHP as an additive has been investigated by Xu et al , who showed that it leads to a stark enhancement in grain size, resulting in V OC s of up to 1.12 V and a maximum efficiency of 17.2% .…”
Section: Resultsmentioning
confidence: 99%
“…59 On the other hand, the addition of MACl as an additive, which also leads to larger grain sizes, has been shown to increase the open-circuit voltage of devices leading to a maximum PCE of 17.7%. 60 The use of AHP as an additive has been investigated by Xu et al, who showed that it leads to a stark enhancement in grain size, resulting in V OC s of up to 1.12 V and a maximum efficiency of 17.2%. 32 The best performing additive, an imidazole sulfonate zwitterion, has also been shown to increase the grain size, with optimum devices exhibiting a V OC of 1.14 V and a PCE of 20.8%, 31 only slightly higher than what is achieved by HPA.…”
Section: Resultsmentioning
confidence: 99%
“…All the XRD patterns of these perovskite materials indicated typical MAPbI 3 crystalline structures with an intense peak of (100) at 2 θ = 14.2° ( ref. 25 ) and no peaks related to the MAPbCl 3 perovskite crystal structure at 2 θ = 15.4° ( ref. 16 ) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%